La planificación didáctica y su incidencia en el proceso educativo de la RED "Las Mercedes", de la parroquia Febres Cordero, cantón Babahoyo, provincia de Los Ríos, año lectivo 2011 - 2012 - Poveda Olalla, Alex Israel (2011)
It recognized the need to plan any human activity without which it is possible to achieve effective and efficient results. In this sense, the teacher can not circumvent this requirement, especially the importance and social impact that she has. Thus, the teacher (according to G. Imideo Nérici) requires unavoidable so plan your work, so you may be able to give adequate answers to the following crucial questions: what to teach, whom to teach, why teach and how to teach. a) What to teach. - is related to the course and the same level and nature of the subject and the content to be treated. This work of selection can not ignore the point of view of the interests of the context and stage of development of the learner. Also, the teacher should take into account the other disciplines and curricular activities in order to articulate the overall planning of the educational institution. b) Who teach. - refers to the type of student which is directed towards education. It refers more to the peculiarities and possibilities of the students, considered as a bio-psychosocial and cultural key aspect of educational planning, and that all work should revolve around this topic. In short, the student is the subject of education, hence its importance. c) Why teach. - This aspect is related to the objectives and competencies to be achieved, and also with the subject that must be developed. It is clear that the subject or matter is the medium to be achieved the goals it sets certain teaching. They are also targets those who point to the justification of the teaching-learning. e) How to teach. - This point is related to instructional methods that teachers should use to achieve the goals it sets. Includes techniques and teaching methods, teaching aids and resources, in general, technology has to be used in the teaching-learning process. So planning is an important and complex task that requires careful preparation of teachers, taking into account each and every one of the elements and components that must intervene in the PEA. Although also be taken into account that all planning is always flexible, this means that may be subject to change according to varying requirements or interest that is present in the classroom or on the occasion of the plan work, ie the planning is not static, necessarily have to be met in one hundred percent. Now, if the conditions allow it to be fulfilled, reaching the objectives or powers provided, will be successful. The following work is structured by strand as follows: It is part of the study that characterizes the problem, objectives, assumptions, and its implementation. Chapter I: that is the theoretical framework underlying the scientific contribution of the subject. Chapter II: establishing the field study to determine the findings and recommendations. Chapter IV: that is the proposal to the problem encountered.